The perceived effects of primary hyperhidrosis on collegiate student-athletes and their sport performance - Zerrudo, Christopher Neil C. 1999-
Hyperhidrosis is a condition characterized by excessive sweating beyond the normal thermoregulation response of the body. Due to the visible and excessive manifestation of sweating in primary hyperhidrosis patients, its physical and mental consequences are evident and can affect the quality of life. But when it comes to the context of sports and sports performance, information is very limited. In this study, the researcher aims to identify and explore the perceived effects of primary hyperhidrosis specifically on collegiate student-athletes and their sports performance making this study significant to coaches, researchers, and especially athletes with primary hyperhidrosis to increase awareness and understanding of the relationship of primary hyperhidrosis and sports that will help sports professionals and the athletes themselves to make informed decisions in terms of managing of the condition and possibly improve sports performance. Data were collected by conducting a semi-structured interview with collegiate student-athletes diagnosed with primary hyperhidrosis from a large public state university in Quezon City. Through the process of thematic analysis, results produced several themes namely Unfamiliarity of Primary Hyperhidrosis, Management Practices, Cause of Embarrassment, Effect on Sports Performance, and A Distraction to Sports. These themes revealed that primary hyperhidrosis has a negative effect on collegiate student-athletes sports participation in terms of their grip that they perceived it to negatively impact their consistency, accuracy, focus, and concentration to their sport. Therefore, it was recommended that sports professionals and athletes take primary hyperhidrosis as a significant factor when it comes to sports and sports performance.